DAMPAK SUPLEMENTASI MAKANAN BERKALSIUM TERHADAP PERTUMBUHAN TULANG ANAK UMUR 9-11 BULAN - Edwi Saraswati; Basuki Budiman (Persagi, 1999)
The Impact of Calcium Supplementation on Skeletal Development of 9-11 Months Children.A study on the effect of calcium supplementation on the bone development of hand and wrist had been carried out in the subdistrict of Kadudampit, Sukabumi, West Java. Sixty children 9-11 months of age who participated in Posyandu from 9 villages were purposively selected as a sample of the study. These children were divided into two groups, i.e.: treatment group received high calcium supplementation in the form of skimmed milk and biscuit, and children in the control group received low biscuit. The supplements were given 12 weeks period. The stage of skeletal development of the individual child was assessed twice, i.e.: at base line and at the end of supplementation period using a portable Min-X-Ray machine type HP-300. The result showed that the milk supplementation was manifested in the increase of calcium intake from 49,2% to 148,9% of the recommended level (RDA). The stage of skeletal development in treatment group is 1,6 times greater than that in the control group. In other words, the skeletal development of children in the treatment group were more advanced that than of children in the control group. It is therefore recommended that besides other micronutrients supplementation, high calcium containing food be given to young children, particularly 6-11 months old.Key words: skeletal development, calcium supplementation